(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Engineered wood must undergo a long period of drying process before it is ready to be used. Therefore, a new heat exchanger technology must be invented to dry the engineered wood more effectively. The quality of the engineered wood is one of the factors influencing the production process. This research was conducted to identify the optimal temperature for drying engineered wood using a cross-flow flat-plate heat exchanger with unmixed fluid arrangement and to determine the heat exchanger’s most efficient number of passes. This research was conducted using the numerical method (CFD simulation) and the Ansys Fluent software. In this research, the viscosity, density, and pressure constant were determined to be at 1 atm. We used air as fluid medium with a mass density of 1,228 kg/m3, air thermal conductivity of 0.0286 W/m.K, fluid viscosity of 2,0349.10-5 N.s/m2, steam mass density of 0.689 kg/m3, and thermal conductivity of 0.0370 W/m.K. Results showed that, in order to increase the air temperature in the drying chamber, heat energy of 69566.01 kJ/s must flow into the flat-plate heat exchanger. Further calculations show that the heat exchanger’s effectiveness (ϵ) was 25% and that the average temperature in the heat exchanger on the air side and the gas side was 68.63 oC and 172.5 oC, respectively.